ANALYSES ON THE DEVELOPMENT OF MENTAREN SWAMP AREA IN PULANG PISAU REGENCY - Miming Virganinda Burako (Jurnal Teknologi Berkelanjutan, 2013)
Mentaren Swamp Area in Pulang Pisau Regency is categorized as less productive and the land usage is not optimal. Initially, Mentaren Swamp Area utilized polder water system, however since the water gate as the primary intake of the channel was broken and unfixed, the water in the area reduced and urge the residing people to open the polder in order that the tide water could penetrate the channel. However, since the polder is now opened, the time and inundation volume has lessened. Due to the change of the water system from polder (closed) to open, an analysis was conducted to identify the current water supply in Mentaren Swamp Area and how much land area that can be handled by existing water discharge. To identify those matters, the analysis was conducted by the following stages: collecting primary and secondary data, conducting Hydrology analysis, and calculating water supply and designing Swamp Development Concept. Those stages were conducted to know how much the expansion of land area is or to alter the land usage so it can be used in developing the Mentaren Swamp area. Based on the Mock method, the annual average supply of water (Q80) of Kahayan Watershed in Central Kalimantan Province for Mentaren Swamp Area of Pulang Pisau Regency is 1,864 m3/second. The current farming land is 534 hectare and can be increased by as much as 731. 39 hectare to 1.265 hectare utilizing rice crops cropping pattern.